THE USE PUZZLE BOARD IN TEACHING ENGLISH YOUNG LEARNERS AT ONE OF PRIMARY SCHOOL IN CIMAHI - Kikit Maulidina; Sudiyono Sudiyono (IKIP Siliwangi, 2022)
Teaching English for elementary school level is very challenging to achieve goals in teaching. Therefore teachers are required to teach optimally according to the very diverse character of students in receiving lessons because currently English in elementary schools is not included in the core subject but is an extracurricular school. Therefore the teacher is expected to provide maximum knowledge in the delivery of the material being taught so that students can meet the needs that will be faced in the future. here the teacher uses media in teaching where the media can make students more active and effective. The purpose of this study was to examine student responses in learning, increase student interest and increase student creativity in learning English. The study was conducted at SD Baros Mandiri 3 Cimahi. The research method used in the research is observation, document analysis, interviews and the media used by the teacher is a puzzle board. The results of this study indicate that the puzzle board media used by the teacher can make students more attractive and creative in learning English. Keywords: Teaching, Young Learners, Media